2020
DOI: 10.1055/s-0040-1708045
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Designing, Conducting and Reporting Observational Studies in Homeopathy

Abstract: Background Randomized placebo-controlled trials are considered to be the gold standard in clinical research and have the highest importance in the hierarchical system of evidence-based medicine. However, from the viewpoint of decision makers, due to lower external validity, practical results of efficacy research are often not in line with the huge investments made over decades. Method We conducted a narrative review. With a special focus on homeopathy, we give an overview on cohort, comparative cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Observational studies provide such prior experience, as they describe "real-world" care settings and allow for a more generalized and robust estimation of effects in clinical practice; they are thus an important approach to assist in designing RCTs. 8 The need is for a series of systematic studies that includes collection and analysis of good-quality cases treated with homeopathy. Prognostic factor research is an important technique for the analysis of cohorts of such cases.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies provide such prior experience, as they describe "real-world" care settings and allow for a more generalized and robust estimation of effects in clinical practice; they are thus an important approach to assist in designing RCTs. 8 The need is for a series of systematic studies that includes collection and analysis of good-quality cases treated with homeopathy. Prognostic factor research is an important technique for the analysis of cohorts of such cases.…”
Section: Introductionmentioning
confidence: 99%
“…For the latter two, aspects of COHERE or AHSURED may be considered. 2,21,26 In ►Table 2, the items in the STROBE-Vet extension correspond to the items in the original STROBE statement, and both follow the typical order of sections within a scientific manuscript. All relevant checklist items need to be addressed within the paper.…”
Section: Discussionmentioning
confidence: 99%
“…5 In-depth information about cohort, cross-sectional and case–control studies can be found in diverse sources. 2 3 4 5 6 7…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies include cross-sectional, case-control, and cohort study designs. 49 50 The methodological strengths of the present study were the enrolment of 202 children, which can be considered a large sample, and the use of standardized assessment tools such as adenoid score, Mallampati score, tonsillar size (a photographic record), SRBD of PSQ, and A/N ratio, regularly evaluated until 12 months. Furthermore, our study represents the first formal assessment of IHMs in ATH.…”
Section: Discussionmentioning
confidence: 99%